Analysis of Islamic Law Regarding Aqiqah Custody in Wedding Ceremonies in Banua Sendana Village, Majene - Agung, Muhammad Agus; Wahidin, Wahidin; Sunuwati; Jamaluddin, Samsidar (Jurnal Marital: Kajian Hukum Keluarga Islam, 2023)
Discusses the analysis of Islamic law regarding leaving aqiqah at weddings in Banua Sendana Village, Majene Regency. The object of this research is the aqiqah entrustment in the Islamic legal analysis of wedding ceremonies. This research aims to find out what the aqiqah deposit system is like in Banua Sendana Village, Majene Regency and what the analysis of Islamic law regarding aqiqah deposits in marriage is. This type of research is a field study that uses qualitative descriptive data. The method used is a normative sociology approach with data collection techniques through observation, interviews and documentation. Meanwhile, data analysis techniques include data identification, data presentation, and drawing conclusions. The results of the research show that the implementation of the aqiqah entrustment was carried out by the people of Banua Sendana Village, namely where they or parents who wanted to perform their child's aqiqah came to the family who would be holding the wedding and brought a certain amount of money. money to be handed over to the family who will be getting married, although there are some families who are getting married who are reluctant to accept gifts of money and at the aqiqah entrustment event it is usually done without any family relations and at the aqiqah event they only slaughter one cow for seven children, where the cow is intended for for aqiqah. and The aqiqah deposit system implemented by the Banua Sendana Village community is in accordance with the views of Islamic law.